Contextualizing Digital Pedagogy: A Virtual Public History Model for Peace and Reconciliation Education in Central Java, Indonesia - Bain Bain; Carolina Santi Muji Utami; Rizka Cahyaning Arifin Putri (Indonesian Journal of History Education, 2025)
This study develops and evaluates a Virtual Public History model for peace education among Central Java high school students. Using Research and Development with the ADDIE model, local narratives of conflict and reconciliation were integrated into an interactive digital platform. Expert validation and limited trials with 25 students revealed a critical paradox: high pedagogical relevance and cultural sensitivity contrasted sharply with infrastructural constraints and low technical feasibility. Findings demonstrate strong demand for contextually resonant peace-oriented content while highlighting persistent digital divides. Contributing to discourse on History Education as Social and Reconciliatory Practice, the study proposes an "offline-first" hybrid implementation strategy. It offers nuanced critique of globally circulating digital pedagogy models, emphasizing necessary adaptation of technological innovations to local socio-material realities in post-colonial societies for sustainable educational impact.